New blue phosphorescence from trifluorosulfonyl-substituted iridium complexes. (April 2019) - Ha, Yeon Hee; Sohn, Sunyoung; Han, Seung-Hoon; Kim, Bong Gon; Ahn, Hyungju; Jung, Sungjune; Kwon, Soon-Ki; Kim, Yun-Hi
Abstract: For color-pure phosphorescence organic light emitting diodes (PHOLEDs), we synthesized the trifluoromethyl sulfonyl substituted ligand and two new blue Iridium complexes with perfluoro-sulfonyl group (SOCF3 pic and SOCF3 mpic). The both iridium complexes showed similar photophysical and thermal properties while the HOMO energy leves of two Iridium complexes slightly differnet to be −5.84 eV for SOCF3 pic and −5.74 eV for SOCF3 mpic, respectively. The device with the SOCF3 mpic dopant exhibited higher device efficiencies of 7.17 cd/A and 3.7% compared to that with the SOCF3 pic dopant (4.03 cd/A and 2.78%). Two-dimensional GIXD images of scattered X-ray intensity from surface to full depth for SOCF3 pic-doped and SOCF3 mpic-doped TCTA:4PTPS films were characterized for preferential orientation along the out-of-plane direction. Graphical abstract: Highlights: Synthesized trifluoromethyl sulfonyl substituent blue phosphorescent dopants. Decreased HOMO level due to a strong electron withdrawing group in the iridium complexes with perfluoro-sulfonyl group. High current and external quantum efficiency of 7.17 cd/A and 3.70% in picolinate doped device with 3-methylpyridine (mpic) as the ancillary ligand. SOCF3 mpic-doped TCTA:4PTPS films has more preferential orientation along the out-of-plane direction.